10‐4: Invited Paper: Taking High Dynamic Range Further: Apple Pro Display XDR. Issue 1 (4th March 2021) - Gu, Mingxia (Vincent); Liu, Ron; Albrecht, Marc; Qi, Jun; Yin, Victor
Abstract : Apple Pro Display XDR, with its industry‐leading high dynamic range performance, is presented. Several optical, mechanical and electrical components of the 2D backlight sub‐system, which is key to enabling HDR, will be reviewed, along with algorithm features implemented within a custom‐designed Timing Controller.